Assessment of oral health-related quality of life in patients receiving corticobasal dental implants - Sanjay K Sahoo; Silpiranjan Mishra; Sangamesh Ningappa Chinnannavar; Atul A Bajoria; Asutosh Das; Dhirendra K Singh (Wolters Kluwer Medknow Publications, 2023)
Background: Among various treatment modalities for tooth replacement, dental implants are considered the best one. This study assessed the effects of smoking, periodontitis, and diabetes on oral health-related quality of life (OHRQoL) in patients receiving corticobasal dental implants. Materials and Methods: One hundred twenty patients of either gender who received corticobasal dental implants were enrolled. All were subjected to Oral Health Impact Profile-20 (OHIP-20) for dental implant patients (OHRQoL questionnaire). The patient satisfaction level was measured on a scale with points ranging from 0 to 5. The value 0 indicates no satisfaction, whereas the value 5 shows highly satisfied. Results: Of 120 patients, males were 70 and females were 50. The overall satisfaction level was 4.92, articulation speech was 4.12, implants were 4.80, and construction was 4.88. The overall satisfaction, articulation speech, implants, and construction values in patients with and without diabetes were 4.90 vs 4.93, 4.56 vs 4.86, 4.76 vs 4.92, and 4.94 vs 4.83, respectively. The overall satisfaction, articulation speech, implants, and construction values in patients with and without smoking were 4.83 vs 4.91, 4.52 vs 4.88, 4.70 vs 4.82, and 4.12 vs 4.84, respectively. The overall satisfaction, articulation speech, implants, and construction values in patients with and without periodontitis were 4.72 vs 4.96, 4.52 vs 4.88, 4.73 vs 4.98, and 4.81 vs 4.95, respectively. The overall satisfaction, articulation speech, implants, and construction values in patients with one to three risk factors and control were 4.85 vs 4.96, 4.82 vs 4.94, 4.88 vs 4.97, and 4.76 vs 4.86, respectively. There was a significant difference in pain, infections and/or swelling, sleeping problems, problems with self-confidence, taste, chewing discomfort and/or difficulties, and influence on food choice before and after in patients treated with corticobasal dental implants (P < 0.05). Conclusion: The satisfaction level is higher after obtaining corticobasal dental implants in patients with diabetes, smoking, and periodontitis as compared to control. Thus, corticobasal dental implants may be considered alternate treatment options for these patients.